Reassessing civil conflicts in Genoa, 1160-1220 - Inguscio, A (2012)
This thesis examines the phenomenon of civil violence in Genoa (1160-1220). Genoese civil conflicts in the period are victim to a historiographical paradox. While their importance for the survival of communal institutions has been frequently underlined, they have often been misrepresented in the historiography. Our current understanding of civil conflicts in Genoa is in need of a reassessment if we want to deepen our comprehension of the history of a city that is considered a key centre and fundamental building bloc in the rise of the European continent to economic prominence. This thesis studies civil violence from a perspective that takes into account the shifting form of Genoese conflicts and their protagonists. The civil conflicts in Genoa saw constant development in their intricacy, nature and participants (Chapter one). I distance myself from the issue of motives and causation, a pursuit which has misled scholars. Instead I focus my attention on the underlying patterns that made conflicts in Genoa possible -- the web of relationships among the families of the Genoese elite – in order to study how the individuals and families that were involved in civil violence made their decisions (Chapter two). The understanding of these links and of the development of conflict in Genoa is an important thread to follow in order to reassess several aspects of the political history of the city between the twelfth and the thirteenth century (Chapter three). In light of my findings, the institutional transition of the city from a commune led by consuls to one led by a foreign podestà (Chapter four) and the Genoese involvement in the Mediterranean scenario (Conclusion), appear shaped by the maturing phenomenon of civil violence. This thesis aims to fill the current gap in academic studies on civil conflict in Genoa and to turn the phenomenon from a footnote to the current historiography into a rich vein of historical understanding of the fundamental dynamics of the city and its development.